Post-COVID-19 Neuronal Complications and Impact of Physical Activity on the Disease Symptoms: A Narrative Review - Ewa Duchnik; Joanna Kruk; Mariola Marchlewicz (Central European Journal of Sport Sciences and Medicine, 2025)
The coronavirus disease 2019 (COVID-19) caused a global health crisis, leading to many pathological alternations regarding cells, tissues, organs, and biological systems. Extensive research during the past three years has revealed that even if symptoms of the COVID-19 infection and disease are not severe, the complications after may be critical. Evidence has indicated that apart from the most characteristic complications caused by COVID-19 infection, such as respiratory tract disorders, severe damage to the central and peripheral nervous systems is possible, resulting in neuronal and mental complications. For this reason, the quality of life of severe COVID-19 survivors requires targeting therapy. The most studies focused on a wide spectrum of COVID-19 complications, however, direct evidence of the virus-specific neuropathogenicity and molecular mechanisms involved in this complication are only emerging. We have actual scientific knowledge of post-COVID-19 neurological complications and provide the current evidence on biological mechanisms operating in this process. This review also aims to present how inflammation and oxidative stress may contribute to the disease severity. Finally, we discuss the use of physical exercise (PE) interventions to reduce physical and mental complications in COVID-19 survivors. Findings show that dysregulation of the immune system is characteristic for COVID-19 disease severity. PE can increase muscle strength, respiratory function, decrease dyspnea, and improve survivors’ quality of life. However, randomized controlled trials and observational studies of higher methodological quality are needed to determine effective, individualized and safe amount of exercise to support the evidence.